REVITALISASI TARI KAIN PADA MASYARAKAT LOKAL DI KELURAHAN BATU URIP KOTA LUBUKLINGGAU SUMATERA SELATAN - Ninda Levia; Nerosti Nerosti; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to analyse the problems that caused the loss of its existence in fabric dance in the community supporters. This type of research is a qualitative descriptive method of analysis. The object of this research is to Dance in rock Fabric Urip Lubuklinggau South Sumatra Province. The type of data in this study is the primary data and secondary data. The main instruments are the researchers themselves. Engineering data collection done by the library, observation, interview and documentation. The data collected was analyzed with techniques of interpretation so that it can be retrieved. The results showed that the revitalization effort underway to lift the back Dance fabric from the village of stone town of Lubuklinggau Urip through coaching and training activities of the Dance Art Studio fabric in Tepak Cindo. Effort to lift back Dance fabrics with ways of processing and dissemination. Processing that is developing a pattern, and modify the costume by adding accessories and a long dress to look attractive. Whereas a Dance fabrics with revitalization efforts of dissemination through training and performances, i.e. reproduce the appearance or extended performances committed by Sanggar Seni Tepak Cindo in the town of Lubuklinggau so that more known more this Fabric as the Dance community identity Neighborhood City Positions Lubuklinggau Stone. Key words: Revitalization, dance fabrics, the process of Socialization.